Big Data Health Care System Using Distributed Wearable Sensors - Vijayalakshmi, A.; John Paul, C. (International Journal of Engineering and Technology, 2018)
The modern world facilitates a luxurious life with more comfort using technology support. The latest developments not only support the human life, but it causes problems to the humans in many ways. The primary concern of Big Data is underway in Healthcare unit. Alerting before occurring of problem is evolved with the help of big data health care solutions.Â Different types of sensors can be integrated with big data to produce a good solution. Our system provides a mechanism for health care systems using hidden Markov model. It acts as an intelligent system. It provides appropriate support and forwarding health related data to do real time analysis for analyzing and understanding health status.Â